Eco-Printing on Cotton Fabric with Natural Indigo Dye Using Wild Taro Corms as a New Thickening Agent. Issue 13 (1st December 2022) - Mongkholrattanasit, Rattanaphol; Klaichoi, Charoon; Rungruangkitkrai, Nattadon; Vuthiganond, Nattaya; Nakpathom, Monthon
ABSTRACT: To solve ecological and toxicological issues related to some synthetic dyestuffs, the potential application of a new thickening agent from wild taro corms and natural indigo dye in the screen printing process of woven cotton and knitted fabrics was investigated in this study. For this purpose, effects of the dye, thickening agent, thiourea dioxide, and sodium hydroxide concentrations were varied and investigated with respect to the color yield, fastness, and physical properties. Results revealed that the printing paste comprising the thickening agent prepared from the modified starch of wild taro corms can be applied for the printing of cotton fabric using natural indigo dye. The colorfastness to washing, water, and perspiration of the printed samples was found to be good to very good, whereas the colorfastness to light and rubbing was mostly at good and fair, respectively. The printed fabric also had increased tensile strength, tear strength, bursting strength, and stiffness compared to the original fabric.